An empirical proposal on power, knowledge and truth of correlations among the minimum wage, foreign direct investment in the industrial sector and export / Kittisak Jermsittiparsert, Thanaporn Sriyakul and Chayongkan Pamornmast - Kittisak, Jermsittiparsert; Thanaporn, Sriyakul; Chayongkan, Pamornmast (Research Management Institute (RMI), 2012)
This research showed the correlations among the minimum wage, foreign direct investment in the industrial sector, and export. These entities were criticized severely by the authorities on the Pua Thai Party's policy announcement on the guarantee oflabors' minimum wage of300 baht/day. The present research then employed an advanced quantitative methodology, analyzing time-series data ofthe minimum wage,foreign direct investment in the industrial sector, and export by regression, the Johansen Cointegration Test, and the Pairwise Granger Causality Test.